21st Century prose and freedom – from the issues of proza środka - Czyżak, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The main aim of the article is a consideration the problems connected with this part of contemporary literature which is called “proza środka” (“prose of the middle”). 21st century novels treated as the examples of this phenomenon (e.g. Lubiewo written by Michał Witkowski, Poczwarka by Dorota Terakowska, Kurator by Zbigniew Kruszyński) and their reception prove that new political situation after 1989 changes the rules of common literary perception. The readers expectations support origination of textes which are ambitious, attractive but also easy to assimilation. The main theme of that part of prose is freedom, especially freedom of the indyvidual.